Interactive Medical Calendar as a Genre of Internet Communication: Russian as a Foreign Language - Oksana V. Dreifeld (Виртуальная коммуникация и социальные сети)
This paper describes the linguo-didactic prospects of using the method of interactive medical calendar to develop an artificial language environment for students who study Russian as a foreign language. It features classifications of medical calendars, their receptive properties, and experience of using them as a linguo-didactic genre in teaching Russian. The authors designed an interactive medical calendar that develops a professional medical jargon in non-Russian speakers at medical institutes. The method proved to be an efficient multimedia tool that unites the realities of medicine and language learning in a new context. It promotes learning by doing and out-of-class practice. The calendar allows non-Russian speakers to use professional terms and activates theoretical knowledge while developing digital skills. It also improves the skill of cross-cultural contacts, encourages informal communication, individualizes the learning process, and increases motivation in mastering both the medical profession and the Russian language. The method of medical calendar is a simple genre that facilitates the academic process of learning Russian as a foreign language by adding new activities and information.